Reporting by Audit Oversight Bodies - World Bank Group (World Bank, Vienna, 2019)
A wave of accounting scandals beginning about fifteen years ago, including Enron, WorldCom, and Parmalat, created a consensus among policymakers across the globe that independent auditors were not adequately challenging the financial reporting by their clients and could not be trusted to regulate themselves. Beginning with the Sarbanes-Oxley Act of 2002 in the U.S., there has been a global movement away from self-regulation of the auditing profession and towards independent oversight. Perhaps the most important milestone in this movement was the 2006 Audit Directive of the European Union, which required all EU members and accession candidates to implement independent oversight. A key goal of independent oversight is to provide relevant and reliable information to investors, lenders, audit committees, regulators, other stakeholders, and the general public about auditors and the audit market, among other matters. This paper aims to provide a brief synopsis on the topic of reporting by audit oversight bodies (AOBs) through their annual and inspection reports. It outlines international principles and legislative requirements, highlights certain good practices and shares results from a focused survey across EU-REPARIS and STAREP countries.